Effect of Vacuum Heat Treatment and Gluten Gddition on the Gel Properties of Tilapia Myofibrillar Protein - Jiahui SUN; Jiaqi FANG; Wei YANG; Guanghua XIA (Shipin gongye ke-ji)
In order to explore the effects of vacuum heat treatment and gluten on the gel properties of myofibrillar protein (MP), the effects of vacuum heat treatment and gluten addition on tilapia MP gel were studied by testing texture, water retention, intermolecular forces and other indicators. Under the condition of water bath, the addition of 0.7% gluten significantly improved the hardness and gel strength of MP. The microstructure results showed that the gluten made the MP gel network tend to be flat and the holes decreased, which was conducive to the formation of gel. Compared with the water bath heating, the cohesion, elasticity and gel strength of MP gel were significantly improved after 1 h of one-stage vacuum heat treatment. After 2 h of vacuum heat treatment, the cohesion and gel strength of MP gel were further improved. In addition, vacuum heat treatment and gluten addition improved the moisture state of MP gel, the content of T22 fixed water decreased, and the migration of T22 fixed water and T23 free water was restricted, resulting in the stability of the moisture in the gel. The results of intermolecular forces showed that the interaction between ionic bond and hydrophobic interaction was enhanced, which promoted the gelation of MP. In summary, vacuum processing promotes the structure extension of MP and the formation of a more compact three-dimensional gel network.